Application of 1, 1‐ADEQUATE and DFT to correct 13C misassignments of carbonyl chemical shifts for carbapenem antibiotics. (20th July 2022) - Cohen, Ryan D.; Wang, Xiao; Sherer, Edward C.; Martin, Gary E.
Abstract: Prior to the development of sensitive proton‐detected 2D NMR experiments, assigning 13 C signals could be a significant challenge, and mistakes have occurred even for prominent compound classes. In this study, 1, 1‐ADEQUATE data were used to unambiguously reassign the 13 C chemical shifts for the β‐lactam carbonyl at the C‐7 position and the proximal carboxylate at the C‐10 position of the carbapenems, meropenem and imipenem. Density functional theory (DFT) was then investigated to provide sufficiently accurate 13 C chemical shift predictions, allowing for the carbonyl signal reassignment of thienamycin. Abstract : 1, 1‐ADEQUATE NMR spectra were used to definitively reassign the 13C signals of the beta‐lactam carbonyl and proximal carboxylate of meropenem and imipenem. DFT calculations were then investigated to provide sufficiently accurate 13C chemical shift predictions for this class of compounds, which allowed for the reassignment of carbonyl signals of thienamycin.